2022
DOI: 10.1021/acs.macromol.2c01691
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics in an Immiscible Polyolefin Blend

Abstract: Motivated by the problem of brittle mechanical behavior in recycled blends of high density polyethylene (HDPE) and isotactic polypropylene (iPP), we employ optical microscopy, rheo-Raman, and differential scanning calorimetry (DSC) to measure the composition dependence of their crystallization kinetics. Raman spectra are analyzed via multivariate curve resolution with alternating least-squares (MCR-ALS) to provide component crystallization values. We find that iPP crystallization behavior varies strongly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…On the other hand, the melting temperature and the degree of crystallinity were lowered mainly for the dispersed phase of the HDPE. It is well known that PP and the HDPE could interfere with each other's crystallization [23][24][25][26][27] , so the presence of the nanoparticles in the blend interface could increase this interference since nucleation at the interface between the two components has been observed by different authors 26,27 . The DMA results can be seen in Figure 9, and the data are summarized in Table 5.…”
Section: Characterization Of Nanocompositesmentioning
confidence: 99%
“…On the other hand, the melting temperature and the degree of crystallinity were lowered mainly for the dispersed phase of the HDPE. It is well known that PP and the HDPE could interfere with each other's crystallization [23][24][25][26][27] , so the presence of the nanoparticles in the blend interface could increase this interference since nucleation at the interface between the two components has been observed by different authors 26,27 . The DMA results can be seen in Figure 9, and the data are summarized in Table 5.…”
Section: Characterization Of Nanocompositesmentioning
confidence: 99%
“…Directly melt mixing and extruding incompatible plastics (such as PE and PP) without any chemical modification often produce a product with poor mechanical properties as a result of immiscibility, phase separation, and lack of crystallization. [12][13][14][15][16][17][18] A common technique to separate plastic wastes is sink/float separation in water to separate polyolefins (mainly PP and PE) from plastics with higher densities (such as PET, PS, and PVC). 9 Near infrared (NIR) is equipped to differentiate polymer types based on characteristic chemical bonds.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is yet difficult to separate PP and PE in a cost-effective and scalable way for their similarities in hydrocarbon backbone structures and densities. 1,17 The increased cost of separating the immiscible constituents can lead to incineration or landfilling of plastic wastes rather than recovered through mechanical route. 6,19 The separated flakes of plastic wastes are fed to an extruder and processed at high temperature and high torque.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical performance of immiscible blends are dependent upon the blend components' crystallisation behaviour and final blend morphology [14][15][16]. Several factors are important for morphology development during polymer processing such as composition, viscosity ratio of the components, interfacial properties, crystallinity and processing conditions [6,14,[17][18][19][20][21][22]. Several studies have reported the mechanical properties, crystallisation behaviour and morphology of PP:PE blends [6,7,11,[22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%